Analisis faktor ASI eksklusif, sanitasi dan pasokan air serta sistem pelayanan kesehatan sebagai penyebab terjadinya stunting di Kota Langsa - Emilda AS Emilda AS; Juliastuti Juliastuti; Silfia Dewi; Lili Kartika Sari Hrp (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The nutritional problem of children under five is still high (Stunting) in Langsa City. The prevalence of stunting in Aceh in babies under two years old (baduta) is 37.9%, while the national prevalence is 30.8%, which means 4 out of 10 babies suffer from stunting. Stunting can be caused by various factors, including direct factors such as family and household factors, adequate additional/complementary food, breastfeeding and infections. Indirect factors such as political economy, health and health services, education, society and culture, agricultural and food systems as well as water, sanitation and the environment.Objectives: Analysis of exclusive breastfeeding, sanitation and water supply and the health service system causing stunting in Langsa City.Methods: Design quantitative, with a sequential cross-sectional design. The research was conducted in Langsa City in 2021 and samples were taken using the total sampling method of 50 respondents according to the data in the Langsa City Health Service e-PPGBM electronic application. The instrument used is a questionnaire, analysis uses the Chi – Square test.Results: Research results from 50 respondents based on stunting problem factors showed the variable exclusive breastfeeding (p= 0.015). Variables sanitation and clean water supply (p= 0.005), health service system (p= 0.006).Conclusion: From the results of the research, there is a close relationship between the direct causes and indirect causes of the occurrence of nutritional/stunting problems in the Langsa City Health Service Work Area in 2021, especially the three variables (exclusive breastfeeding, health service system, and sanitation and water supply).